2012
DOI: 10.3402/pba.v2i0.18052
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes in innate immune phenotype and function in rhesus macaques (Macaca mulatta)

Abstract: Aged individuals are more susceptible to infections due to a general decline in immune function broadly referred to as immune senescence. While age-related changes in the adaptive immune system are well documented, aging of the innate immune system remains less well understood, particularly in nonhuman primates. A more robust understanding of age-related changes in innate immune function would provide mechanistic insight into the increased susceptibility of the elderly to infection. Rhesus macaques have proved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 58 publications
10
59
1
Order By: Relevance
“…For IL-8, middle-aged monkeys averaged 242 ± 179 pg/mL, which was significantly lower than for all of the old monkeys (data not shown). These serum IL-8 values are comparable to other recent reports of adult macaques (Asquith et al 2012). IL-10 in the middle-aged monkeys (mean, 3.03±5.06 pg/mL) did not differ from the older monkeys in either diet condition.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…For IL-8, middle-aged monkeys averaged 242 ± 179 pg/mL, which was significantly lower than for all of the old monkeys (data not shown). These serum IL-8 values are comparable to other recent reports of adult macaques (Asquith et al 2012). IL-10 in the middle-aged monkeys (mean, 3.03±5.06 pg/mL) did not differ from the older monkeys in either diet condition.…”
Section: Resultssupporting
confidence: 91%
“…These nutritional effects on cytokine concentrations were not due to CR-induced reductions in age-related morbidity or visceral fat (Colman et al 2009). The occurrence of such high IL-8 values in the aged monkeys was unexpected, but the range determined for middle-aged monkeys was comparable to a recent report (Asquith et al 2012), suggesting that the IL-8 was accurately determined.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…During immune reconstitution the ratios of naive, EM and CM shift, resulting in the EM population dominating the CD8 T cell compartment and CM population dominating the CD4 T cell compartment. These changes are similar to those observed with ageing in RM, where EM T cells relatively outnumber the naive and CM T cells within the CD8 subset while CM T cells are the dominant memory population in the CD4 subset [84]. These changes are probably the result of increased levels of homeostatic proliferation [61,85].…”
Section: Discussionsupporting
confidence: 77%
“…The 2003 outbreak in the USA caused by prairie dogs infected by imported exotic pets from Africa clearly showed that monkeypox is not restricted to Africa and can be transmitted at any time to any place (Centers for Disease, C. a. P., 2003;Reed et al, 2004). So far, no licensed antiviral treatment for poxvirus infections is available.…”
Section: Introductionmentioning
confidence: 99%